Vulnerable population to COVID-19 according to the prevalence of non-communicable diseases in Cienfuegos - Alder León Brito (Medisur)
Background: The identification of spaces with high concentrations of people with risk factors for COVID-19, such as non-communicable diseases, allows more accurate decision-making in the work of facing the spread of the virus and safeguarding human lives. Objective: to analyze the vulnerable population distribution to COVID-19 according to the prevalence of non-communicable diseases. Methods: descriptive, cross-sectional study, of a geographic-epidemiological nature, in the Cienfuegos province. The weighting of thematic maps of distribution of patients with prevalence of noncommunicable diseases was applied, in age groups from 25 to 59 and 60 years and over, using multi-criteria evaluation techniques in geographic information systems. Synthesis maps were prepared with the stratification of health areas in five degrees of population vulnerability to COVID-19. Results: the most vulnerable health areas were: “Cecilio Ruiz de Zárate”, from the Cienfuegos municipality in the aged group 25 to 59, and “Aracelio Rodríguez Iglesias”, from Cumanayagua, in the 60 years of age and more. Conclusion: the most vulnerable health areas were identified in the Cienfuegos municipalities of greater economic importance; especially in the Cienfuegos city, in the oldest part, more densely populated and with the greatest number of services, all of which implies an extra risk, since the SARS-CoV-2 virus spreads easily, live a greater number of vulnerable people to COVID-19.